FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERILAKU PERAWAT DALAM PENERAPAN MANAJEMEN K3 DI RUANG RAWAT INAP - rina diana sihombing; Daniel Ginting; Henny Arwina Bangun (Jurnal Endurance, 2022)
Occupational Diseases in hospitals can attack all workers,both medical, and non-medical people who have the risk of being exposed to hazardous biological materials,contact with disposable medical devices. Efforts to control, minimize the risk of work accidents, it is necessary to have good management of Hospital K3 management.The purpose of the study was to analyze the factors that influence the behavior of nurses in the application of K3 management in the inpatient ward of RSUD RM. Djoelham Binjai. research is explanatory research. The time of the study was from January to July 2022.The population of all nurses in the RSUD was 111 people. The sample was taken using purposive sampling as many as 53 people in all inpatient rooms inpatient care.Enabling factors(safety, security facilities,rules/policies do not affect thebehavior of nurses in the application of K3management.Reinforcing (supervision) factors affect the behavior of nurses in the application of K3 management. It is recommended that the hospital director be able tomake SOPpolicies and guidelines and sanctions regarding K3 supervision. For officers to supervise theimplementation of K3 management for nurses to behave safely when providing medical services and following policies and SOPs, given awards in order to cultivate OSH behavior in their respective work units.